Effects of Malaysian Kelulut Honey on Osteoblastic Proliferation of MC3T3-E1 Cells (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Malaysian Kelulut Honey (MKH) is a well-recognized Malaysian honey and has gained widespread popularity due to its ability to promote health. Numerous scientific studies have been conducted to prove the health benefits of MKH; however, its bone-protective effects have not yet been well-studied. Osteoblasts are vital cells for bone formation; thus, it is important to study the effect of MKH on osteoblasts for a better understanding of bone formation. This study was conducted to evaluate the effects of MKH on the proliferation of bone-forming cells using MC3T3-E1 cells. The cytotoxicity and proliferation of MKH on MC3T3-E1 cells were assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay and the bromodeoxyuridine (BrdU) assay. The cells were treated with MKH at various concentrations ranging from 0.001% v/v to 10.0% v/v for 24, 48, and 72 hours. The results demonstrated that MKH at 0.01% v/v significantly enhanced proliferation by 131.65% (p
Keywords: Malaysian Kelulut Honey; Osteoblasts; MC3T3-E1 Cells; Proliferation; Cell viability